Synthetic Organic Compounds From Paper Industry Wastes: Integrated Biotechnological Interventions - Jaiswal, Shweta; Kumar Gupta, Guddu; Panchal, Kusum; Mandeep,; Shukla, Pratyoosh (Frontiers in Bioengineering and Biotechnology, 2021)
SOCs (Synthetic organic compounds) are reported as xenobiotics compounds contaminating the environment from various sources including pulp and paper industries wastes. Since, the demand and production of paper is growing increasingly, the release of paper and pulp industrial waste consisting SOCs is also increasing the SOCs pollution in natural reservoirs to create environmental pollution. In pulp and paper industries, the SOCs viz. phenol compounds, furans, dioxins, benzene compounds etc. are produced during bleaching phase of pulp treatment and they are principal components of industrial discharge. This review gives an overview of various biotechnological interventions for paper mill waste effluent management and elimination strategies. Further, the review also gives the insight overview of various ways to restrict SOCs release in natural reservoirs, its limitations and integrated approaches for SOCs bioremediation using engineered microbial approaches. Furthermore, a brief overview of sustainable remediation of SOCs via genetically modified biological agents including bioengineering system innovation at industry level before waste discharge are also covered in this review.